THE BATTLE OF KURSK: HOW THE WESTERN HISTORIANS APPRECIATE IT - A. A. Paderin (Vestnik MGIMO-Universiteta)
In the article the author analyses how the largest battle of the Great Patriotic War and the second World War, the Battle of Kursk, is shown in the west historiography: the intentions of the opposite sides, the degree of preparation to the coming battle, the correlation between number of people and military machines, the realization of decreed tasks, the peculiarities of strategy and moving fighting forces for the battle, the mistakes of German side which were the result of defeat. There are some arguments that the foundation for the forming ideas of western historians about the events on the Soviet German front in summer 1943 is in the workings of captured German generals and officers which were prepared by the task of military – historical service of US army. The workings played the important ideological and methodological role. Trying to excuse themselves these authors explained the defeat of Wehrmacht using some accidental factors which were not connected with their activity as military leaders. In particular there were some mistakes of the highest German political and military leadership, climatic and geographical peculiarities of the war in Russia. In the article the controversial battle Western historians, forms, methods and means of falsification of history and the role of the battle; exposure technique attempts to distort the essence of the events and the outcome of the battle.